Bonding of the polymer polyetheretherketone (PEEK) to human dentin: Effect of surface treatments - Rocha, Regina Furbino Villefort [UNESP]; Anami, Lilian Costa [UNESP]; Campos, Tiago Moreira Bastos; de Melo, Renata Marques [UNESP]; e Souza, Rodrigo Othávio de Assunção; Bottino, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2016)
Polyetheretherketone (PEEK) is a material suitable for frameworks of fixed dental prostheses. The effect of different surface treatments on the bond strength of PEEK bonded to human dentin was evaluated. One hundred PEEK cylinders (3 mm×3 mm) were divided into five groups according to surface treatment: silica coating, sandblasting with 45 μm Al2O3 particles, etching with 98% sulfuric acid for 5, 30 and for 60 s. These cylinders were luted with resin cement onto 50 human molars. First, each tooth was embedded in epoxy resin and the buccal dentin surface was exposed. Then, two delimited dentin areas (∅:3 mm) per tooth were etched with 35% phosphoric acid and bonded with a two-step self-priming adhesive system. After the luting procedure the specimens were stored in water (24 h/37 °C). Shear bond strength (SBS) was tested using a universal testing machine (crosshead speed 0.5 mm/min; load cell 50 kgf) and failure types were assessed. Stress data (MPa) were analyzed using the Kruskal-Wallis test. Comparison of the proportions of different failure types was performed using the Bonferroni method (p<0.05). Kruskal-Wallis demonstrated that differences among groups were not significant (p=0.187). Mean SBS were as follows: silica coating, 2.12 ± 1.12 MPa; sandblasting, 2.37 ± 0.86 MPa; sulfuric acid 5 s, 2.28 ± 1.75 MPa; sulfuric acid 30 s, 1.80 ± 0.85 MPa; sulfuric acid 60 s, 1.67 ± 0.94 MPa. Adhesive and mixed failures were predominant in all groups. Both physical and chemical surface treatments produced adhesion between PEEK, resin cement and dentin.
Keywords: Dental prosthesis; Polyetheretherketone; Polymers; Resin cements; Shear strength